Study of misfit dislocations by EBIC, CL and HRTEM in GaAs/InGaAs lattice-strained multi-quantum well p-i-n solar cells - Mazzer, M. (Institutional Knowledge at Singapore Management University, 1996)
The location, density and nature of misfit dislocations (MDs) in lattice-strained multi-quantum well (MQW) structures were investigated by depth-resolved electron-beam-induced current (EBIC) and cathodoluminescence (CL) modes in a scanning electron microscope. A planar network of dark recombination lines due to MDs was observed at the lower and upper interfaces of the MQW stack. Their density was correlated with the MQW average strain before relaxation, giving information on the equilibrium and catastrophic strain relaxation processes which take place at the two MQW stack interfaces. High-resolution transmission electron microscopy (HRTEM) showed the location and nature of the MDs at an atomic level; they are mostly close to the lower MQW stack interface, on a {111} plane constituting glissile-60 degrees dislocations, composed of two partials including a stacking fault. Comparison of their density with the dark line density indicates that each dark line represents a group of about 9 MDs. Quantitative information on the electrical properties of solar cells was obtained by (i) determining the average MD contrast at the lower MWQ interface using EBIC gain measurements and (ii) establishing the existence of a strong correlation between the dark current in forward bias and the MD density.